INHIBITION OF ENZYME ACTIVITY OF Β – GLUCOSIDASETO PRODUCTION OF EXO -1, 4 – β – GLUCOSIDASEEXTRACTION FROM Trichoderme Viride - Al-Temimi, Ali (Iraqi Journal of Science, 2024)
The aim of this work was to inhibition of the enzyme β–glucosidase for theproduction of the enzyme Exo-1, 4-β-glucosidase that have the power for analysis ofcellulose to glucose. The using of the inhibition substance D- glucano - δ - Lactonsuccess to inhibition of β–glucosidase at the concentration 0.45 mg/mL. at 1 minute.The optimum circumstances temperature, pH, and time of fermentation were (45min., 4.8, 8 day).